Population Genetic Analysis and Sub-Structuring of Theileria annulata in Sudan - Salih, Diaeldin A.; Ali, Awadia M.; Njahira, Moses; Taha, Khalid M.; Mohammed, Mohammed S.; Mwacharo, Joram M.; Mbole-Kariuki, Ndila; El Hussein, Abdelrhim M.; Bishop, Richard; Skilton, Robert (Frontiers in Genetics, 2021)
Tropical theileriosis, caused by Theileria annulata, is a major obstacle for improvement of cattle production in Sudan. The disease is endemic in the north and central regions of Sudan. Due to changes in tick vector distribution and animal movement, outbreaks of the disease have been reported outside the known endemic areas, in east and west regions of the country. To control the disease, a live schizont attenuated vaccines have been developed based on tissue culture technique. Before the vaccines are deployed there is need to genotype the parasite in the field as well as the vaccine strain, in order to be able to monitor any breakthrough or breakdown, if any, after the deployment of the vaccine in the field. A total of 246 field samples positive for T. annulata DNA and the vaccine strain were genotyped using nine microsatellite markers. High multiplicity of infection was reported from north and central populations compared to east and west populations. Principal components analysis revealed two sub-structures with a mix of all four populations in both clusters and the vaccine strain used being aligned with left-lower cluster. Linkage analysis indicated that only the north population was in linkage disequilibrium, while other populations were in linkage equilibrium, and when all isolates were treated as single population linkage disequilibrium was indicated. Nei genetic identity between the vaccine and field samples ranged between 0.62 with north and 0.39 with west population. Overall T. annulata genetic analyses of four populations in Sudan exhibited evidence of extensive intermixing with only two groups being observed that are independent of geographic origin, but a high level of genetic diversity within each population in the four geographically separated regions studied. The result suggests that the live schizont attenuated vaccine, Atbara strain may be suitable for deployment in all regions where tropical theileriosis occurs in Sudan.